Menggunakan Konsep Inkarnasi Yesus sebagai Model Penginjilan Multikultural - Febriaman Lalaziduhu Harefa (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2020)
The Indonesian nation is a nation that has differences in religion, ethnicity and race, which is exposed from Sabang to Merauke. Indonesia is also known as a maritime country because most of its territory is ocean and has thousands of islands, with various geographical conditions in it. It is this superiority that makes the Indonesian nation a great and authoritative nation and respected by the international community. This fact also makes the Indonesian nation known as a muticultural nation. Therefore the aim of this study is to find an appropriate evangelistic model to be applied in the context of a multicultural Indonesian nation. So that the Gospel of the Kingdom of God can be preached efficiently without causing conflicts between Evangelists and UPG (Unreached People Groups). So in this study used a qualitative method with a descriptive-theological approach. The results found three models of evangelism in the context of the Indonesian nation, namely the model of building family relationships with UPG (Unreached People Groups), the service model fighting for the values ??of equality-justice and freedom, and the service model of gospel dialogue-proclamation